(untitled) (Polis (Santiago), 2019)
Modeling and simulation with agents is a third way of doing science, and its potential lies not in prediction, but in the understanding of fundamental processes of complex phenomena. How can agent-based computational modeling and simulation help social sciences study complex phenomena? The assumption is that it allows artificial societies to study the emergence of phenomena, and to establish links between theoretical assumptions and empirical facts. Moreover, agentbased models make it possible to study emerging behaviors at the macro level by studying micro -bottom up- behaviors. In this respect, this document aims to construct an initial state of the art in this topic. The challenges and pending problems are located in the empirical validation, in this sense the statistical estimation and the accompanied modeling are the main approaches.